Recurrent Auricular Pseudocyst: Successful Treatment Using a Dental Silicon Cast - Yusuke Yoshioka; Takeshi Namiki; Tsukasa Ugajin; Hiroo Yokozeki; Atsushi Tanaka (Karger Publishers, 2021)
Auricular pseudocysts (APs) are benign intercartilaginous cysts at the auricle. Various therapeutic options have been used to treat APs, but they frequently recur in usual clinical practice. Here, we report a case of AP successfully treated using a silicon cast. A 65-year-old male presented with a cyst on his right auricle. Although a local injection of steroid was administered, the cyst had recurred. A dental silicon cast was applied after removal of the contents of the cyst by suction. There was no recurrence of the cyst 6 years after that treatment. Dental silicon casts are a novel technique for an appropriate fixation over auricles in the treatment of APs and had an effective therapeutic result in our case.